Amlodipine-induced generalised exfoliative dermatitis: not to be missed! - Che' Man, Mohamad; Adanan, Nur Azizah; Che Alhadi, Shahidah; Amiruddin, Salman (Universiti Kuala Lumpur (UniKL), 2025)
Amlodipine a calcium channel blocker (CCB), is commonly used in treating hypertension, coronary artery disease, and chronic kidney disease. It is considered a first-line treatment for high blood pressure. Amlodipine acts by selectively inhibiting voltage-gated L-type calcium ion channels, which consequently decreases systemic vascular resistance, total vascular resistance, and muscle contractility. We report a case of amlodipine-induced exfoliative dermatitis, highlighting the importance of recognizing this rare but serious cutaneous reaction to amlodipine, a commonly used drug in primary care. Prompt discontinuation of the offending drug and appropriate management are crucial for improving patient outcomes. Clinicians should maintain a high index of suspicion for drug-induced exfoliative dermatitis in patients presenting with generalized erythema and scaling after initiating new medications